Systematic Literature Review on the Development of Augmented Reality-Based Learning Materials to Enhance Students' Critical Thinking Skills in Senior High School Education - Ningsi, Surya; Danial, Muhammad; Aryani, Farida; Husain, Halimah (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to systematically review the development of Augmented Reality (AR)-based learning materials to enhance students’ critical thinking skills in Senior High School Education. In the context of 21st-century education, critical thinking skills are essential competencies for facing global challenges and technological advances. The integration of AR technology in learning materials provides interactive and contextual learning experiences that foster active student engagement. This study employs the Systematic Literature Review (SLR) method with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Of the 100 identified articles, 20 met the inclusion criteria, focusing on AR implementation in teaching materials to enhance critical thinking. The synthesis results indicate that AR-based learning materials significantly improve critical thinking indicators such as analysis, evaluation, and reflection through immersive learning experiences. Furthermore, AR strengthens motivation, conceptual understanding, and collaborative skills. This study highlights the importance of designing AR-based digital learning materials integrated with reflective pedagogy and constructivist theory, particularly in Senior High School Education, to prepare students as critical, creative, and adaptive learners in the digital era.